2009
DOI: 10.5688/aj7306105
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate and Postgraduate Pharmacy Students' Perceptions of Plagiarism and Academic Honesty

Abstract: Objectives. To assess undergraduate and postgraduate pharmacy students' perceptions of plagiarism and academic honesty. Methods. A questionnaire was administered to undergraduate and postgraduate pharmacy students to determine their levels of awareness of university policy concerning academic honesty; attitudes to plagiarism by rating the acceptability of a range of plagiarizing and cheating practices; and choice of appropriate penalties for a first and second occurrence. The choice of behaviors in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 14 publications
(27 reference statements)
7
87
1
3
Order By: Relevance
“…However, the current results were inconsistent with Ryan et al [21] results in Australia who study the knowledge and awareness of students about plagiarism, reported that the awareness level was high while the knowledge level was low.…”
Section: Discussioncontrasting
confidence: 57%
“…However, the current results were inconsistent with Ryan et al [21] results in Australia who study the knowledge and awareness of students about plagiarism, reported that the awareness level was high while the knowledge level was low.…”
Section: Discussioncontrasting
confidence: 57%
“…That is, if our respondents lacked a clear interpretation of the concept of plagiarism, as a consequence the students (as a group) may have indicated attitudes toward highly divergent activities (e.g., copying full papers; copying taking paragraphs of text word-for-word without proper acknowledgement of the source; copying even a single sentence word-for-word without acknowledging the source; paraphrasing without acknowledgement of the source). If this was the case, arguably better psychometric results of the scale may be attained with a more informed participant sample (such as post-graduate students, who are suggested to be better informed on matters of plagiarism than undergraduates; see Ryan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that a study conducted on medical students found no differences in cheating in connection with either attitude or responses to behavioral scenarios (Rennie & Rudland 2003). It is further interesting that other studies did not factor in possible gender differences in their study design (Bates et al 2005;Harries & Rutter 2005;Ryan et al 2009;Muhney et al 2008). These studies add credence to the idea that more focused research is required in this area.…”
Section: Gender and Course Differencesmentioning
confidence: 99%
“…To measure self-reported engagement in academic dishonesty, students were asked to respond to 32 items regarding specific behaviors often cited in the literature in the area of academic dishonesty (Anderson & Obenshain 1994;Coverdale & Henning 1998;Howe et al 2000;Aggarwal et al 2002;Harries & Rutter 2005;Marshall & Garry 2005;Muhney et al 2008;Ryan et al 2009). The items were selected and appraised by a research panel of five academics who have an interest in academic dishonesty and the items were then randomly placed within the 32-item questionnaire.…”
Section: Methodsmentioning
confidence: 99%